Laboratory experiments for basic chemistry - Moh, Pak Yan (Universiti Malaysia Sabah, 2005)
This manual contains six experiments covering four major areas of chemistry: physical, organic, inorganic, and analytical chemistry. The experiments are able to provide the students with skills and knowledge of handling, interpreting, and reporting chemical experiments. Each laboratory experiment in this manual comprises three major parts that are arranged systematically. Students are required to answer the pre-lab review prior to doing their experiment by following the proposed procedures. After the experiment, each student is required to produce a lab report and answer the post-lab questions in the results and discussions section.